The effects of attention in auditory–visual integration revealed by time-varying networks - Jiang, Yuhao; Qiao, Rui; Shi, Yupan; Tang, Yi; Hou, Zhengjun; Tian, Yin (Frontiers in Neuroscience, 2023)
Attention and audiovisual integration are crucial subjects in the field of brain information processing. A large number of previous studies have sought to determine the relationship between them through specific experiments, but failed to reach a unified conclusion. The reported studies explored the relationship through the frameworks of early, late, and parallel integration, though network analysis has been employed sparingly. In this study, we employed time-varying network analysis, which offers a comprehensive and dynamic insight into cognitive processing, to explore the relationship between attention and auditory-visual integration. The combination of high spatial resolution functional magnetic resonance imaging (fMRI) and high temporal resolution electroencephalography (EEG) was used. Task-related fMRI activations were mainly observed the bilateral temporoparietal junction (TPJ), superior temporal gyrus (STG), primary visual and auditory areas, which were selected as regions of interesting (ROIs) for nodes of time-varying network. The electrical activity of the auditory-visual cortex was estimated via the normalized minimum norm estimation (MNE) source localization method. Finally, variations in node connections as revealed by the constructed time-varying network confirmed the theory that auditory-visual integration occurred before attention, aligning with the early integration framework.